Evaluation of the Sorbent Properties of Single‐ and Multiwalled Carbon Nanotubes for Volatile Organic Compounds through Thermal Desorption–Gas Chromatography/Mass Spectrometry. Issue 8 (2nd April 2015) - Wong, Gwendeline K. S.; Lim, Li Zhen; Lim, Marcus Jun Wen; Ong, Li Lin; Khezri, Bahareh; Pumera, Martin; Webster, Richard D.
Abstract Carbon nanotubes (CNTs) possess well‐defined structural and chemical characteristics coupled with a large surface area that makes them ideal as sorbent materials for applications where adsorption processes are required. The adsorption properties of carboxylated derivatives of multiwalled carbon nanotubes (COOH‐MWCNT) and singlewalled carbon nanotubes (COOH‐SWCNT), together with their nonfunctionalized counterparts (MWCNT and SWCNT) for 48 common atmospheric volatile organic compounds (VOCs) were determined using thermal desorption–gas chromatography/mass spectrometry (TD‐GCMS). The CNTs exhibited similar recoveries for many of the VOCs compared to the standard sorbent materials, Carbopack X and Tenax TA. However, VOCs with electron donor–acceptor (EDA) properties such as carbonyls, alkenes, and alcohols exhibited poorer recoveries on all CNTs compared to Carbopack X and Tenax TA. The poor recoveries of VOCs from the CNTs has important implications for the long term use and storage of CNTs, because it demonstrates that they will become progressively more contaminated with common atmospheric VOCs, therefore potentially affecting their surface‐based properties.